“Vamos brincar de Brasil?/ Mas sou eu quem manda”: estudo sobre a poética de Raul Bopp - Cunha, Yasmeen Pereira da (2019)
This work carried out the study of the complete poetry of the modernist poet Raul Bopp, seeking to make explicit his relations with the popular. The study of the theme "popular culture" in the work of the poet is not random. It can be affirmed that the great majority of the critical studies on the author elect him like a poet "typically" Brazilian. The adjective is given because such a theme is a constant in Boppian poetics. One sees, therefore, that there is a correspondence between national and popular, and the poetry of the author in question offers aesthetic and historical indications that reaffirm this correspondence. From the assumptions of dialectical critique, which indicate that social and historical contexts are stimuli for literary production, one of the issues addressed in this work is that "popular subjects" were assimilated by Modernism not only as a reaction to Parnassianism and Symbolism, but also because they were in the period of an emerging social content, especially in relation to the formation of the working class, the Brazilian labor movement and the populist government of Getúlio Vargas. In this way, aesthetic resources inherited from cubism and surrealism, as well as characteristics of popular literature and popular imagination in general, will be used by Raul Bopp to represent the image of a precarious country, even if the techniques used point superficially to an optimistic view of the country. All Bopp's work, then, aesthetically formalizes specific tensions of various historical periods of Brazil. There will be recurrent images of the Negro, the country, rural areas, added to the images of trains, roads, automobiles, coexisting in a contradictory way. The Brazil that the lyrical subject of the poems builds is a country shaped by what is popular, heir of a slave past that echoes in the present. The updates of social patterns typical of the colonial past run through the poetry of Raul Bopp, making evident that it is necessary to understand the past, to transform the present.